Below the Line: an Analysis of Income Poverty in New Zealand, 1984 - 1998 - Stephens, Robert; Frater, Paul; Waldegrave, Charles (School of Management Working Papers, 2000)
The economic and social reforms between 1984 and 1999 led to claims of increasing economic hardship, a widening income distribution and adverse consequences on living standards from higher housing costs. This article provides a systematic discussion of those claims, based on an analysis of Statistics New Zealand annual Household Economic Survey. Using a focus group determined poverty line, the paper explores who was poor in 1998, as well as commenting on trends in poverty between 1984 and 1998, on both the basis of disposable income and when this poverty measure is adjusted for relative housing costs. Trends in the incidence and severity of poverty depend crucially on whether an absolute or relative approach is taken to adjusting the poverty line through time. Key Words: Poverty, focus groups, income distribution, trends.